Investigations of single crystals of the ternary compound CuIn7S11 - V. V. Shatalova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
With the method of directional solidification (vertical Bridgman method) single crystals CuIn7S11 are grown. Their composition, structure and electrical properties are determined. According to the transmission spectra in the fundamental absorption edge at 80 and 295 K the bandgap is determined. The researches of thermal expansion and calculation of thermodynamic parametres are held by the dilatometric method.